Key questions in ecology a study and revision guide - Rees, Paul A. (CAB International, 2021)
"This book is intended as a study and revision guide for students following programmes of study in which ecology is an important component. It contains 500 multiple-choice questions (and answers) set at three levels - foundation, intermediate and advanced"--
Includes bibliographical references and index
Keywords: Ökologie; Ecology; Lehrbuch